1994
DOI: 10.1002/j.1460-2075.1994.tb06765.x
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria toxin at low pH depolarizes the membrane, increases the membrane conductance and induces a new type of ion channel in Vero cells.

Abstract: Receptor‐dependent translocation of diphtheria toxin across the surface membrane of Vero cells was studied using patch clamp techniques. Translocation was induced by exposing cells with surface‐bound toxin to low pH. Whole cell current and voltage clamp recordings showed that toxin translocation was associated with membrane depolarization and increased membrane conductance. The conductance increase was voltage independent, with a reversal potential of approximately 15 mV. This value was unaffected by changing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
4
29
0
Order By: Relevance
“…The basic protocol for measuring current in these experiments represents a sensitive assay for pore formation in plasma membranes by PA and could probably be adapted for other pore-forming bacterial toxins (33,34). This whole-cell technique may ultimately prove suitable for the study of catalytic factor translocation.…”
Section: Discussionmentioning
confidence: 99%
“…The basic protocol for measuring current in these experiments represents a sensitive assay for pore formation in plasma membranes by PA and could probably be adapted for other pore-forming bacterial toxins (33,34). This whole-cell technique may ultimately prove suitable for the study of catalytic factor translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in planar lipid bilayers have shown that under low pH conditions (pH Յ 6) in the cis compartment (the compartment to which protein is added), the isolated T domain is able to form cation-selective channels in the membrane (10); similar channels are formed by whole DT and by a truncated mutant, DT(CϩT), lacking the R domain (10,11). Channels are also formed in plasma membranes at low pH by the whole toxin or the B fragment (12,13). Two long hydrophobic helices (TH8 and TH9) buried within the native T domain insert into the bilayer when the domain converts to a transmembrane form (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…By using whole cells exposed to low pH after DT binding at 4°C, mimicking the endosome environment (33,34), the toxin can be translocated directly from the cell surface to the cytosol when cells are incubated at 37°C. DT-induced pore formation has also been studied by measuring ion conductance or the release of radioactive ions from cells (35)(36)(37). By using these systems, the T domain of fragment B was shown to be important for insertion and translocation of fragment A.…”
mentioning
confidence: 99%